Knowledge, attitudes and practices of biosecurity and biological risk standards in private dentists of three cities of Nicaragua - Paz Betanco, Manuel Amed (2019)
Objective: Describe the knowledge and performance of biosecurity and biological risk standards of dentists in private practices from three cities of Nicaragua; during the year 2017. Methods: A transversal descriptive study was implemented on 86 dentists selected with the snowball technique through a non-probabilistic sampling and for convenience, in the cities of Managua, Chinandega and León; a previously validated semi-structured questionnaire was applied. The data was processed using descriptive statistics through frequencies and percentages of the variables under study. Results: The dentists know the concept of biological risk in 98.8%, but not the specific name of the infectious agents and their entrance pathway into the host (76.7%), however, they perform frequent hand washing before and after each dental procedure (60.4%) and have basic notions of the protocol to follow when percutaneous accidents happen in 48.8%; the majority demonstrated good performance during disinfection and sterilization of instruments and equipment 78% and 68.6%, as well as personal biosecurity (98.8%). The city of Managua stands out for the adequate management of bio-infectious waste. Conclusions: Dentists presented a regular knowledge, fair performance and good biosecurity practices. Keywords: Health knowledge, attitudes, practice; Biosafety; Dentistry; Nicaragua.